Perspektif Gen Z Terhadap Perkembangan dan Esensi Ulos Batak Toba di Era Globalisasi - Ririn Agustine; Salsabilla Ifanda Lubis; Gustianingsih (Universitas Cenderawasih, 2024)
This research discusses the importance of Ulos Batak Toba in globalization and the important role of Gen Z in understanding, maintaining, and promoting it. Ulos, a typical Toba Batak woven fabric, has a very important cultural value, but modernization has reduced its importance. Generation Z is more likely to perceive Ulos as old-fashioned and visually unappealing, posing a threat to its preservation. This research studies the different types of Ulos in Toba Batak and their important role in daily life and cultural beliefs. Ulos represent celebratory symbolism, high values, and cultural identity for the Batak people. As agents of change in the digital era, Gen Z bears the responsibility to preserve Ulos, although their modernistic views and disregard for tradition jeopardize its preservation. This research aims to trace the development of Ulos in social, historical, and symbolic frameworks, and explore how Gen Z's perspective impacts the sustainability of Ulos in the midst of globalization. Conducted through a literature review approach, this research emphasizes the need for comprehensive education and socialization on the cultural values embedded in Ulos, and highlights the potential of Gen Z to actively preserve this heritage.